THU0292 Diagnostic experiences of patients with psoriatic arthritis: misdiagnosis is common. (12th June 2018) - Ogdie, A.; Nowell, W.B.; Applegate, E.; Gavigan, K.; Venkatachalam, S.; de la Cruz, M.; Flood, E.; Schwartz, E.J.; Romero, B.; Hur, P.
Abstract : Background: Psoriatic arthritis (PsA) is a heterogeneous, chronic, immune-mediated disease characterised by a range of musculoskeletal conditions including joint pain, swelling, enthesitis and dactylitis as well as skin and nail manifestations. Early diagnosis of PsA is important as shorter time to treatment may improves outcomes. 1 However, PsA is often undiagnosed or misdiagnosed. 2 There is limited information on the diagnostic experiences of patients with PsA, including medical care sought and potential barriers to diagnosis. Objectives: To determine patients' experiences related to the diagnosis of PsA including initial symptoms experienced, medical care sought, and time to diagnosis. Methods: US patients aged ≥18 years with a self-reported diagnosis of PsA were recruited through CreakyJoints (www.Creakyjoints.org), an online patient support community comprising patients with arthritis and arthritis-related diseases and their caregivers, and outreach through social media. Participants completed an online survey designed to collect data on socio-demographics, clinical symptoms, disease burden, and diagnosis history, including initial PsA symptoms experienced, types of health care providers seen, misdiagnoses received before a diagnosis of PsA, and time to PsA diagnosis. Survey questions were developed following analysis of qualitative interviews of patients with PsA and clinical experts, as well as a targeted literature review. Results: Of the 203 patients included in the study, 172 (85%) were female, with a mean (SD) age of 51.6 (10.8) years; 132 patients (65%) had private insurance, 61 (30%) Medicare, and 25 (12%) Medicaid. The most common initial symptoms that led patients to seek medical attention were joint pain (142 patients [70%]), stiffness (109 [54%]), swollen joints (101 [50%]), skin rash/psoriasis (97 [48%]), and fatigue (96 [47%]). Most patients (153 [75%]) sought medical treatment within 2 years of symptom onset. During the diagnosis process, patients most commonly sought care from a general practitioner (162 [80%]), rheumatologist (135 [66%]), dermatologist (67 [33%]), orthopedist (44 [22%]), and/or podiatrist (25 [12%]). Only 8 patients (4%) reported that they had never received a misdiagnosis; common misdiagnoses were psychosomatic disease, osteoarthritis, and anxiety/depression (figure 1). Patients reported median (IQR) time since diagnosis of 6.0 (2–11.5) years. Many patients (94 [51%]) received a diagnosis of PsA ≤1 year after seeking medical attention; however, 25 (17%) and 31 (15%) patients received a PsA diagnosis ≥5 and>10 years after seeking medical attention for the first time, respectively. Conclusions: This study showed that patients often had substantial delays and misdiagnoses before they received a PsA diagnosis. Increased understanding of the diagnostic barriers may lead to earlier diagnosis and appropriate treatment that may improve outcomes. References: [1] Haroon M, et al. Ann Rheum Dis2015;74(6):1045–1050. [2] Mease P, Armstrong A. Drugs2014;74(4):423–441. Acknowledgements: This study was sponsored by Novartis Pharmaceuticals Corporation, East Hanover, NJ. Disclosure of Interest: A. Ogdie Grant/research support from: Pfizer and Novartis, Consultant for: Abbvie, BMS, Eli Lilly and Company, Novartis, Takeda, and Pfizer, W. B. Nowell Employee of: Global Healthy Living Foundation, E. Applegate: None declared, K. Gavigan Employee of: Global Healthy Living Foundation, S. Venkatachalam Employee of: Global Healthy Living Foundation, M. de la Cruz Employee of: ICON, E. Flood Employee of: ICON, E. Schwartz Employee of: ICON, B. Romero Employee of: ICON, P. Hur Employee of: Novartis Pharmaceuticals Corporation